Deterioration in health-related quality of life is associated with lower lung resection rates in older adults. Issue 3 (April 2021) - Blakely, Andrew M.; Hu, Hengrui; Wong, F. Lennie; Raz, Dan; Erhunmwunsee, Loretta; Kim, Jae Y.; Sun, Virginia
Abstract: Background: Lung cancer disproportionately affects older adults. Surgical treatment may result in decreased functional status and health-related quality of life (HRQOL). Population-based data about patient-reported health outcomes for patients with early-stage lung cancer who do not undergo surgery is lacking. Methods: We identified lung cancer patients with localized disease from the SEER-Medicare Health Outcomes Survey (MHOS) linked database. Patients with baseline HRQOL survey prior to cancer diagnosis and follow-up survey ≥1 year after diagnosis were selected. Generalized estimating equation (GEE) model was used to compare patients who underwent surgery versus those who did not by demographics and HRQOL measures. Results: Overall, 108 patients were evaluated, of whom 75 (69%) underwent surgery. Surgical patients were younger (mean 73 versus 80 years, p  < 0.001); otherwise, patient groups were similar. Surgery was not performed based on surgeon recommendation ( n  = 21, 64%), contraindication(s), or patients' decision. Both groups experienced similar declines in physical HRQOL, mental HRQOL, and activities of daily living (ADL) scores; and increased major comorbidities. However, non-surgical patients had significant declines in mobility and personal care activities compared to surgical counterparts. On GEE, non-surgical patients were significantly more likely to experience an increase in number of comorbidities (OR 3.3, p  = 0.02) compared to surgical patients. Conclusions: Patients undergoing lung cancer surgery experience significant declines in functional status and HRQOL. However, similar declines are seen in non-surgical patients. More information is needed about long term QOL trajectories with and without surgery so that patients and surgeons can make informed decisions balancing survival benefit and QOL interests.